2022
DOI: 10.1186/s13619-022-00110-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic application of chick early amniotic fluid: effective rescue of acute myocardial ischemic injury by intravenous administration

Abstract: Myocardial regeneration has been considered a promising option for the treatment of adult myocardial injuries. Previously, a chick early amniotic fluid (ceAF) preparation was shown to contain growth-related factors that promoted embryonic growth and cellular proliferation, though the nature of the components within ceAF were not fully defined. Here we tested whether this ceAF preparation is similarly effective in the promotion of myocardial regeneration, which could provide an alternative therapeutic for inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Furthermore, these fluids have low immunogenicity, anti-inflammation, and non-inflammatory features. Our previous studies also demonstrate the promising therapeutic potential of ceAF against cutaneous wound healing and myocardial infarctions [ 32 , 33 ]. Several in vivo experiments show that their tumor tropism has opened new horizons for cancer cell therapies [ 34 ].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, these fluids have low immunogenicity, anti-inflammation, and non-inflammatory features. Our previous studies also demonstrate the promising therapeutic potential of ceAF against cutaneous wound healing and myocardial infarctions [ 32 , 33 ]. Several in vivo experiments show that their tumor tropism has opened new horizons for cancer cell therapies [ 34 ].…”
Section: Discussionmentioning
confidence: 91%
“…Our previous study indicated that ceAF can effectively rescue heart function after acute myocardial ischemic injury by intravenous administration in mice and swine ( 22 ). However, the active component was still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation and separation of ceAF from 7-days chick embryo were performed as previously described ( 22 ). Briefly, the eggs impregnated with male seed were incubated at ∼38°C with 50% humidity for 7 days ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al describes the cardioprotective effects of the main active component, peak 8 (P8) fraction, from Chick early amniotic fluid (ceAF). In a previous study, the authors discovered that ceAF is very effective in the rescue of myocardial injury, in mice and pigs models of IR injury ( 1 ). In the present topic, they demonstrate that P8 treatment was able to decrease apoptosis in vitro in human embryonic stem cell-derived cardiomyocytes subjected to hypoxia and reoxygenation.…”
Section: Natural Protectionmentioning
confidence: 99%